Tanggung Jawab Pemimpin Dalam Perspektif Hadis - Nyak Maysa (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
This study aims to analyze the responsibility of leaders from the perspective of Hadith using a qualitative library research approach. The primary sources are canonical Hadith collections, supported by classical commentaries and contemporary scholarly articles. Thematic analysis reveals that leadership responsibility encompasses protecting the people, fulfilling communal rights, upholding justice, and ensuring public welfare. The findings further highlight the relevance of Prophetic teachings on leadership to modern good governance discourse, particularly in terms of accountability and ethical governance. This study contributes to the broader field of Islamic political ethics by offering a normative yet contextually applicable framework for leadership in contemporary societies.